Loeffler’s Endocarditis – Unforgiving Eosinophilic Damage to the Endocardium - Ajay Sinha; Pramod Kumar; Saket Sharma; Shraddha Ranjan (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging)
Hypereosinophilic syndrome (HES) is defined as hypereosinophilia due to any cause (absolute eosinophil count > 1500 cells/μL) in the peripheral blood, which leads to eosinophil-mediated multiorgan damage. Cardiac involvement is a significant cause of morbidity and mortality among patients with HES. Here, we discuss a case of eosinophilia-related endomyocardial involvement, also known as Loeffler’s endocarditis, a rare form of restrictive cardiomyopathy. Notably, on genetic analysis, he was found to have a rare FIP1-like-1-platelet-derived growth factor receptor alpha-associated myeloproliferative variant of HES, which responded to imatinib, making it one of the very few reported cases of such kind.